Image Construction as a Strategy of Resistance by Progressive Community Organizations - George, Purnima; Moffatt, Ken; Barnoff, Lisa; Coleman, Brienne; Paton, Cathy (Nouvelles pratiques sociales, 2009)
This article presents research findings on image construction as a strategy of resistance used by progressive community agencies to be responsive to the increasing marginalization of their service users in current times. The agencies project nuanced images in representing their work to service users, funders and stakeholders and community partner agencies. These nuanced images serve to demonstrate the multiple and complex identities of these agencies. The agencies have used this strategy successfully to reclaim their power with funders and use their power effectively in making their services responsive and relevant to the situations of service users. The article provides an interesting presentation on the dynamics of the use of this strategy by progressive community organizations.